DE LA LITERATURA AL CINE. NADA MENOS QUE TODO UN HOMBRE, DE MIGUEL DE UNAMUNO EN LA GRAN PANTALLA MEXICANA. - Núñez-Preza, Noelia (Revista Chilena de Literatura, 2025)
The objective of this paper is to analyze the Mexican films inspired by Nada menos que todo un hombre (1916), by Miguel de Unamuno. The study aims to review the relationship between the novel and the films La entrega (1954), by Julián Soler, and Todo un hombre (1982), by Rafael Villaseñor Kuri, as well as the mechanism that have intervened in the transfer of the literary text to cinematic texts.